Audio-Visual-Based Learning Media through Canva Application for Eight Grade Students - Annisa Ramadina Andani Putri; Marhamah (Universitas Pendidikan Ganesha, 2022)
Audio-visual media can facilitate the interaction between teachers and students during learning activities in the classroom. This study aims to develop of audio-visual-based learning media through Canva Application. This research method is research and development (R&D) which include research and information collection, planning, developing the product, and field testing. The subjects in this research are: material expert, media expert, language expert, learning expert and 36 students in 8th grade. Likert questioner is used in this study. After the product was developed, a feasibility assessment was carried out by experts to see the feasibility of media design, material completeness, language suitability, and feasibility in learning. The results findings were: first the experts’ assessments on the content of audio-visual-based learning media through the Canva Application, it obtained a score of 91.5%. Student responses obtained a score of 90.5%. It can be conclude that the Audio- visual-based learning media is effective because it can increase student learning motivation and can be used in learning.